Identification and Characterization of a Novel Hepta-Segmented dsRNA Virus From the Phytopathogenic Fungus Colletotrichum fructicola - Zhai, Lifeng; Zhang, Meixin; Hong, Ni; Xiao, Feng; Fu, Min; Xiang, Jun; Wang, Guoping (Frontiers in Microbiology, 2018)
A novel hepta-segmented double-stranded RNA (dsRNA) virus was isolated and characterized from the strain FJ-4 of the phytopathogenic fungus Colletotrichum fructicola, and was named Colletotrichum fructicola chrysovirus 1 (CfCV1). The full-length cDNAs of dsRNA1–7 were 3620, 2801, 2687, 2437, 1750, 1536, and 1211 bp, respectively. The 5′- and 3′-untranslated regions of the seven dsRNAs share highly similar internal sequence and contain conserved sequence stretches, indicating that they have a common virus origin. The 5′-and 3′-UTRs of the seven dsRNAs were predicted to fold into stable stem-loop structures. CfCV1 contains spherical virions that are 35 nm in diameter consisting of seven segments. The largest dsRNA of CfCV1 encodes an RNA-dependent RNA polymerase (RdRp), and the second dsRNA encodes a viral capsid protein (CP). The dsRNA5 encodes a C2H2-type zinc finger protein containing an R-rich region and a G-rich region. The smallest dsRNA is a satellite-like RNA. The functions of the other proteins encoded by dsRNA3, dsRNA4, dsRNA6 are unknown. Phylogenetic analysis, based on RdRp and CP, indicated that CfCV1 is phylogenetically related to Botryosphaeria dothidea chrysovirus 1 (BdCV1), and Penicillium janczewskii chrysovirus 2 (PjCV2), a cluster of an independent cluster Ⅱ group in the family Chrysoviridae. Importantly, all the seven segments of CfCV1 were transmitted successfully to other virus-free strains with an all-or-none fashion. CfCV1 exerts minor influence on the growth of C. fructicola but can confer hypovirulence to the fungal host. To our knowledge, this is the first report of a hepta-segmented tentative chrysovirus in C. fructicola.